As implicações do bloqueio do ramo esquerdo no desempenho cardiovascular de pacientes com função sistólica esquerda preservada - Barros, Milena Santos (2013)
Presence of left bundle branch block (LBBB), regardless of evidence of heart disease, increases cardiovascular mortality and morbidity. Isolated LBBB induces ventricular septal asynchrony, it can cause repercussions in left ventricular (LV) function and diameter, which may evolve into ventricular remodeling and heart failure. Cardiopulmonary exercise test (CPET) is a noninvasive diagnostic method and physiological, that simultaneously evaluates cardiovascular and respiratory functions, fundamental to understanding the mechanisms of exercise limitation.. This study sought to evaluate the implications of isolated LBBB to cardiovascular performance in patients with preserved LV systolic function and absence of myocardial ischemia. This is an observational, cross-sectional analysis, which evaluated 02 groups: LBBB (26 patients) and control (23 patients). All patients showed LV systolic function > 50% and myocardial ischemia was excluded through the physical stress echocardiography. They underwent CPET. At statistical analysis, we chose the general linear model, specifically multivariate analysis of covariance (MANCOVA) in which the dependent variables were the parameters of CPET and fixed factors were the LBBB and sedentary lifestyle. The results showed that the percentage of predicted peak oxygen pulse (O2P) in the LBBB group was 98.6 ± 18.6% versus 109.9 ± 13.5% (p = 0.02); the percentage of predicted peak oxygen consumption (VO2) in patients with LBBB was 87.2 ± 15.0% versus 105.0 ± 15.6% (p <0.0001); the percentage of predicted anaerobic threshold VO2 in LBBB group was 67.9 ± 13.6 % versus 70.2 ± 12.8% (p = 0.55); in the LBBB group, ΔVO2/Δwork rate was 15.5 ± 5.5 ml.min-1.watts-1 versus 20.7 ± 7.3 ml.min-1.watts-1 (p = 0.006); the VE/VCO2 slope in LBBB group was 29.8 ± 2.9 versus 26.2 ± 2.9 (p = 0.0001) and T1/2 VO2 was the LBBB group of 85.2 ± 11.8 seconds versus 71.5 ± 11.0 seconds (p = 0.0001). By MANCOVA, adjusting the intervention of sedentary lifestyle and covariates, it was showed that patients with LBBB with preserved left systolic function and absence of myocardial ischemia, showed increase in the VE/VCO2 slope, but the LBBB did not affect aerobic performance. Further studies are needed to elucidate whether the VE/VCO2 slope will be an earlier marker of ventricular dysfunction in patients with LBBB.